Thoracoabdominal trauma: Improved Diagnosis and Management Algorithm - Khodzhimatov Gulomidin Minkhodzhievich; Nosirov Muzaffar Madaminovich; Yakhyoev Sardorbek Mamasobir ugli (Genius Journals, 2024)
The study is based on the results of surgical treatment of 190 patients with thoracoabdominal injuries. The main group consisted of 68 patients, and the improved surgical algorithm was used in the stages of their diagnosis and treatment, the comparison group consisted of 122 patients, and traditional standard methods of diagnosis and treatment were used. In the study, improved surgical tactics were proven to be highly effective for thoracoabdominal injuried patients.
Keywords: thoracoabdominal injuries; laparascopy